Urbanization and the challenges of sustainable transportation: a developing country perspective - Bununu, Yakubu Aliyu (2015)
A major requirement in the development of a sustainable urban transportation system is the reduction of automobile dependence. This paper focuses on the ownership and use of private vehicles in the city of Kaduna in North West Nigeria. Travel behavior data used in the study was obtained through a city - wide socio - demographic and household travel characteristics survey that made use of structured questionnaires and the analysis employed was mainly descriptive statistical analyses. Spatio - temporal data used in the analysis of urban growth was obtained from remote sensing sources. The results show a city experiencing rapid urbanization and population growth alongside high level of private motorized vehicle owners hip and use . The paper concludes by highlighting the environmental, human health and social effects of rapid urbanization and increase in the use of motorized modes of transportation.